From Diagnosis to Lifestyle The Impact of Sports on MODY Diabetes Management - Gała, Kamil; Pilarski, Konrad; Kucharski, Adam; Makuch, Rafał; Chrościcka , Alicja; Czajka, Andrzej; Lenard, Paweł; Michalska, Sara; Dewicka, Martyna; Wawrzyniak, Alicja Maria (Quality in Sport, 2024)
Introduction and objectives: Diabetes is a group of diseases that is currently estimated to affect approximately 537 million adults worldwide. Diabetes can develop due to many factors, including autoimmunity, genetics and insulin resistance. The presented article will discuss the type of monogenic diabetes - maturity onset diabetes in young. This is a relatively rare form of diabetes, affecting no more than 5% of patients with the disease, but it is important to correctly differentiate it and implement appropriate therapy to prevent the development of complications. In addition, the article discusses a group of antidiabetic drugs - sulfonylurea derivatives, which are widely used in diabetic patients. Review and methods: Review and summary of studies and scientific articles avaliable in open-source format on Google Scholar and PubMed. Abbreviated description of the state of knowledge: The diagnosis of MODY diabetes is more extensive than that of the most common types in the population - type 1 and type 2 diabetes. Individual forms of MODY diabetes differ in the location of the mutation in the genome. As a result, the MODY group is heterogeneous, with individuals differing in the severity of symptoms, the treatment used and the presence of developmental abnormalities affecting various organ systems. Sulfonylurea derivatives are a group of drugs that have been used to treat diabetes since the mid-20th century. Their mechanism of action is to stimulate insulin secretion, so it is necessary to preserve at least some of the function of the beta cells in the pancreatic islets when using them. Summary: A collection of information on MODY diabetes is presented based on a review of research and scientific articles. In addition, the section on sulfonylureas provides an overview of first- and second-generation drugs and compares them. The article also highlights the important role of physical activity in managing diabetes and preventing complications.